Day 4 Wed, December 09, 2015 2015
DOI: 10.2523/iptc-18394-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Collective Clay Stabilizers Review

Abstract: Oil and gas fields encounter issues associated with clay minerals through drilling and production. Depending on the types of clay minerals, they pose the danger of swelling and migration upon exposure to incompatible water. Drilling introduces water through drilling mud, and production introduces water through different treatments such as acid stimulation and hydraulic fracturing.The recovery of oil and gas from subterranean formations has been troublesome in formations that contain water-sensitive minerals, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…When zeta potential becomes highly negative or positive (ζ-potential < −20 or ζ-potential > 20), it produces a significant repulsive force with similarly charged particles in solution. Sandstone formation rocks are negatively charged and having a highly negative zeta potential value causes colloidal induced detachment of fines [ 65 , 66 ]. In other words, this highly negative value of zeta potential will increase the repulsive colloidal forces, which triggers the fines migration cases.…”
Section: Resultsmentioning
confidence: 99%
“…When zeta potential becomes highly negative or positive (ζ-potential < −20 or ζ-potential > 20), it produces a significant repulsive force with similarly charged particles in solution. Sandstone formation rocks are negatively charged and having a highly negative zeta potential value causes colloidal induced detachment of fines [ 65 , 66 ]. In other words, this highly negative value of zeta potential will increase the repulsive colloidal forces, which triggers the fines migration cases.…”
Section: Resultsmentioning
confidence: 99%
“…Carried out studies [4] showed that adsorption of quaternary polyamines on bentonite molecules is four times higher than polyacrylamide [5]. Numerous studies carried out worldwide [5,6] as well as authors own studies confirmed effectiveness of ammonium chloride as ionic inhibitor of clay rock hydration. However, application of ammonium chloride in the mud with high pH value is very limited due to possibility of ammonia release.…”
Section: Introductionmentioning
confidence: 85%
“…Those muds contain in its formula, amine agents, among others: tetra alkyl ammonium salts, polyamine acids, polyhydroxylated alkyl ammonium salts, hexamethylenediamine, polyetherdiamines, lipophilic amines [2] as well as cationic polymers [3]. Carried out studies [4] showed that adsorption of quaternary polyamines on bentonite molecules is four times higher than polyacrylamide [5]. Numerous studies carried out worldwide [5,6] as well as authors own studies confirmed effectiveness of ammonium chloride as ionic inhibitor of clay rock hydration.…”
Section: Introductionmentioning
confidence: 87%
“…Cations are then attracted to the silica surface, leading to hydration or dislodgement. 84,85 This section will discuss the intricacies of the clay structure, testing protocols for assessing clay damage, chemicals used to manage impacts of clay damage, and opportunities for optimizing these chemicals. 5.1.…”
Section: Clay Stabilizersmentioning
confidence: 99%
“…86 Pore swelling occurs from surface hydration, cation exchange, and osmotic swelling mechanisms. 85 Migration of clay fines occurs through dislodging and dispersing of clay minerals from the structure caused by fluid movement. 84,87 Crystalline phyllosilicate clay structures consist of alternating SiO 4 tetrahedra and AlO 6 octahedra (i.e., gibbsite) lamina that are stacked in either a 1:1 (i.e., kaolin) or 2:1 (i.e., chlorite, illite, and smectite) ratio to form the unit layer (Figure 5).…”
Section: Clay Stabilizersmentioning
confidence: 99%